2003
DOI: 10.1016/s1535-6108(03)00308-8
|View full text |Cite
|
Sign up to set email alerts
|

p21Waf1/Cip1 as a therapeutic target in breast and other cancers

Abstract: The cyclin kinase inhibitor p21, originally described as a universal inhibitor of cyclin-dependent kinases, has since been shown to have additional functions other than CDK inhibition. It is likely that a key role of p21 is to keep cells alive after DNA damage and subsequent p53 induction, in order for the cell to effect repairs. Thus, the increase in p21 seen in some cancers may impart these cells with a survival advantage. Here we discuss how this antiapoptotic aspect of p21 makes it an attractive target for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
246
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(260 citation statements)
references
References 48 publications
13
246
0
1
Order By: Relevance
“…p21 has been suggested to have a crucial role in maintaining cell viability upon p53 induction and induction of p21 has been shown to impart cells with a survival advantage [32]. Indeed, we showed that the induction of p21 in response to cucurbitacins was reproducibly higher in HCT116 than in Hke-3 cells (Fig.…”
Section: Induction Of P53 and P21 By Cucurbitacins Is Enhanced In Celmentioning
confidence: 66%
“…p21 has been suggested to have a crucial role in maintaining cell viability upon p53 induction and induction of p21 has been shown to impart cells with a survival advantage [32]. Indeed, we showed that the induction of p21 in response to cucurbitacins was reproducibly higher in HCT116 than in Hke-3 cells (Fig.…”
Section: Induction Of P53 and P21 By Cucurbitacins Is Enhanced In Celmentioning
confidence: 66%
“…Several recent studies have demonstrated that p53-dependent p21 induction inhibits the apoptotic response, and p21 attenuation may make genotoxic chemotherapeutic agents more effective by subverting the normal repair process or, more directly, by promoting the apoptotic process through inhibition of p21 interaction with apoptosis signal-regulating kinase 1, which is upstream of JNK (Asada et al, 1999;Gartel and Tyner, 2002;Weiss, 2003). In our condition, CDDP/triptolide combination attenuated p53 downstream molecules such as p21, MDM2 and Puma which have short half-lives for mRNA and protein, but had no remarkable influence on the expression of Bax, which has relatively longer half-life, and activated JNK evoked mitochondrial apoptosis using Bax transactivation as a proapoptotic mediator.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicates that control of p21 expression and regulation of its subcellular localization play a central role in cell fate determination in response to several antiproliferative signals. 42 If so, p16 upregulation would initiate cell cycle arrest and apoptosis signals as p53 activation does, and in both cases p21 function would decide the fate of cells. However, we cannot discern whether p21 suppression of p16-induced apoptosis is the result of a direct antiapoptotic function of p21 or whether suppression of apoptosis is dependent on inhibition of CDK2.…”
Section: Discussionmentioning
confidence: 99%